1962
DOI: 10.1901/jeab.1962.5-167
|View full text |Cite
|
Sign up to set email alerts
|

Stimulus Functions in Chained Fixed‐interval Schedules

Abstract: Pigeons were required to complete three successive fixed-interval components to obtain food.When the same exteroceptive stimulus was correlated with the three components, responding was positively accelerated between food deliveries. When different exteroceptive stimuli were correlated with each component in a fixed sequence, prolonged pauses developed in the first component; low response rates developed in the second component; and responding was positively accelerated in the second and third components. When… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

8
66
1
2

Year Published

1965
1965
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(77 citation statements)
references
References 3 publications
8
66
1
2
Order By: Relevance
“…Other studies have reported very weak responding in early components of a simple chain fixed-interval schedule (e.g., Catania et al 1980, Davison 1974, Williams 1994review in Kelleher & Gollub 1962). These studies found that chains with as few as three fixed-interval 60-s links (Kelleher & Fry 1962) occasionally produce extreme pausing in the first link. No formal theory of the kind that has proliferated to explain behavior on concurrent chain schedules (discussed below) has been offered to account for these strange results, even though they have been well known for many years.…”
Section: Chain Schedulesmentioning
confidence: 97%
See 1 more Smart Citation
“…Other studies have reported very weak responding in early components of a simple chain fixed-interval schedule (e.g., Catania et al 1980, Davison 1974, Williams 1994review in Kelleher & Gollub 1962). These studies found that chains with as few as three fixed-interval 60-s links (Kelleher & Fry 1962) occasionally produce extreme pausing in the first link. No formal theory of the kind that has proliferated to explain behavior on concurrent chain schedules (discussed below) has been offered to account for these strange results, even though they have been well known for many years.…”
Section: Chain Schedulesmentioning
confidence: 97%
“…Conversely, the stimulus at the end of the chain that is actually paired with primary reinforcement is assumed to be a conditioned reinforcer; stimuli in the middle sustain responding because they lead to production of a conditioned reinforcer (Catania et al 1980, Kelleher & Gollub 1962. Pairing also explains why behavior is maintained on tandem and scrambled-stimuli chains (Kelleher & Fry 1962). In both cases the stimuli early in the chain are either invariably (tandem) or occasionally (scrambled-stimulus) paired with primary reinforcement.…”
Section: Chain Schedulesmentioning
confidence: 99%
“…Some data from two-component chained schedules have been consistent with such a prediction, but in cases where more than two components were involved ("extended" chains), empirical studies have typically shown the rate of responding in the initial component to be lower than that under a tandem schedule, in which no changes in stimulation were provided (Gollub, 1977). This finding has been obtained both with chained fixed-interval (Gollub, 1958;Kelleher & Fry, 1962;Thomas, 1967) and with chained fixed-ratio schedules (Jwaideh, 1973;Thomas, 1964). Often the deficiency in responding has been interpreted as showing that the second, or even the third, stimulus in the sequence is ineffective as a reinforcer.…”
mentioning
confidence: 90%
“…Segal, 1965). Thus, the stimulus correlated with the earliest link of a long chain may be nonreinforcing, or aversive (Kelleher & Fry, 1962). Schedule preference studies (e.g., Findley, 1958) also indicate that stimuli associated with large behavior requirements are less positively reinforcing than stimuli associated with smaller behavior requirements.…”
mentioning
confidence: 99%